(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
The study of the understanding of mathematical concepts is of great interest for research in Mathematics Education. In this sense, an investigation is carried out on the understanding of the concept of improper integral, a basic concept from the first courses of Bachelor of Mathematics for subsequent courses. The objective is to characterize the understanding of this mathematical concept through a proficiency model for this purpose, an instrument was designed that was applied to second-year university students. The research is qualitative exploratory and is based on the framework of the Theory of records of semiotic representations.